The concept of food in European Union law in the context of short supply chains and local food systems - Kapała, Anna (Przegląd Prawa Rolnego, 2025)
The aim of this article is to answer the question of whether the existing conceptual categories of food in European Union law, both the general ones such as an “agricultural product” or a “foodstuff” as well as the specific categories such as a “mountain product” are adequate for describing food in short food supply chains (SFSCs) and local food systems (LFSs). It has been concluded that the existing concepts do not reflect the specificity of products offered either under the LFSs or the SFSCs system. This lack of clarity hinders not only their effective promotion through legal instruments but also their recognition in the market. Therefore, the author proposes the introduction of new categories in EU law, such as “local product,” “product directly from the farmer,” or “product from short food supply chains,” along with a voluntary labelling system based on producer self-monitoring. This system would enable consumers to make informed choices and to strengthen the development of local and sustainable food systems.